Characterizing genetic variants for DAG and IP3 signalling pathways in severe cases of coronary spastic angina. (25th November 2020) - Shibutani, S; Yonekura, M; Nosaka, M; Kawamura, Y; Hanada, K; Kasai, S; Yokota, T; Higuma, T; Itoh, K; Tomita, H
Abstract: Background: We previously reported that the activity of phospholipase C (PLC), a key molecule for intracellular calcium signaling, was enhanced in patients with coronary spastic angina (CSA). Furthermore, we found PLC-δ1 864 G to A mutation in about 10% of the male CSA patients. However, comprehensive understanding of genetic role in the pathogenesis of CSA remains to be elucidated. Purpose: We tested the hypothesis that variants in the genes responsible for contraction signaling, especially a Ca2+-dependent mechanism, plays an important role in the pathogenesis of CSA. Methods and results: Exome sequencing was performed to genotype comprehensively CSA cohort, enabling investigation of 258 gene network for diacylglycerol (DAG) and inositol trisphosphate (IP3) signallings, which are responsible for contraction signaling in the vascular smooth muscle cell (VSMC) by a Ca2+-dependent mechanism. The study population included 30 Japanese patients with severe cases of CSA (18 men and 12 women with a mean age of 62.2±10.1 years). In 23 patients, ST segment elevation was recorded on the electrocardiogram during a spontaneous attack. In other 3 patients, ventricular fibrillation occurred following CSA attacks. The rests were diagnosed by ECG changes and elevated cardiac enzymes following CSA attacks. Genetic information from these CSA patients were compared with those from 914 healthy controls. Frequencies of 17 common, functional polymorphisms of DAG and IP3 signallings were statistically similar to those of healthy controls. By high-quality (Call Quality ≥20, Read Depth ≥10), and predicted-deleterious (CADD score ≥20) filterings, the number of the candidate genes were narrowed from 234, 445 to 17, 738, and by selecting genes for DAG and IP3 signallings, further narrowed to 208 genes. Compared with 914 healthy controls, DAG and IP3 signalling genes revealed 26 variants in 15 genes in CSA cases, and by further filtering for rare (914 healthy control frequency <1%), 21 variants in 12 genes were found. They shared variants in G protein subunit alpha q (GNAQ), phospholipase C beta 3 (PLCB3), inositol 1, 4, 5-trisphosphate receptor type 3 (ITPR3), glutamate ionotropic receptor NMDA type subunit 2D (GRIN2D) in ≥5 cases. By filtering for high-quality, predicted-deleterious, and rare, genetic variants related with DAG and IP3 signalling were more found in severe CSA patients compared with healthy controls (CSA 4.33/person vs healthy controls 2.60 /person). Conclusions: These findings indicate genetic heterogeneity in CSA susceptibility and a likely polygenic basis, giving a cumulative effect on DAG and IP3 signalling pathways in a subset of individual CSA patients. Study of larger cohorts is warranted to define genetic risk factors for CSA. Funding Acknowledgement: Type of funding source: None